Dataset on the phagocytic and oxidative capacity of monocytes and granulocytes in the combined therapy of S.aureus infection in mice - Tamara A. Bukeyeva; Sabina G. Murzageldinova; Aray A. Serikbay; Arkadiy V. Krasnoshtanov; Ilya S. Korotetskiy (Data in Brief, 2023)
The aim of this study was to evaluate phagocytic and oxidative activities of monocytes and granulocytes during combined therapy of mice infected by drug-resistant Staphylococcus aureus SCAID OTT1-2022. The treatment of the infected mice was conducted by using an iodine-containing coordination compound CC-195, antibiotic cefazolin and by a combined therapy with CC-195 and cefazolin. The PHAGOTEST and BURSTTEST kits (BD Biosciences, USA) were used to determine the phagocytic and oxidative activities. The samples were analyzed on a FACSCalibur flow cytometer (BD Biosciences, United States). It was found that the different treatment regiments applied on the infected animals caused a statistically significant differentiation in numbers and activity of monocytes and granulocytes in comparison to the negative and positive control animals (intact and infected but untreated mice, respectively).